2022
DOI: 10.3389/fpsyt.2022.899729
|View full text |Cite
|
Sign up to set email alerts
|

A voice recognition-based digital cognitive screener for dementia detection in the community: Development and validation study

Abstract: IntroductionTo facilitate community-based dementia screening, we developed a voice recognition-based digital cognitive screener (digital cognitive screener, DCS). This proof-of-concept study aimed to investigate the reliability, validity as well as the feasibility of the DCS among community-dwelling older adults in China.MethodsEligible participants completed demographic, clinical, and the DCS. Diagnosis of mild cognitive impairment (MCI) and dementia was made based on the Montreal Cognitive Assessment (MoCA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…41,42 Speech data obtained by the DCS can also be used in studies that focus on differences in vocal abilities of participants responding to cognitive testing. 14 In future investigations, it may be worthwhile to explore the development of a composite index In conclusion, our findings demonstrated that the DCS was an effective and efficient tool for case-finding of dementia and MCI in a Chinese community. The large-scale implementation of the DCS among older…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…41,42 Speech data obtained by the DCS can also be used in studies that focus on differences in vocal abilities of participants responding to cognitive testing. 14 In future investigations, it may be worthwhile to explore the development of a composite index In conclusion, our findings demonstrated that the DCS was an effective and efficient tool for case-finding of dementia and MCI in a Chinese community. The large-scale implementation of the DCS among older…”
Section: Discussionmentioning
confidence: 67%
“…A previous study also found an area under the receiver operating characteristics curve (AUC) of 0.95 (95% CI: 0.90, 0.99) for dementia with an optimal cutoff of 7/8, and an AUC of 0.77 (95% CI: 0.67, 0.86) for MCI with an optimal cutoff of 8/9. More details on the DCS development can be found elsewhere 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other tests such as CogEvo [ 21 ], although suitable for the detection of early stages of cognitive impairment, focus only on the analysis of the cognitive areas of orientation and attentional processes. As the detection of MCI is complex, not all tools are suitable for it, with some tools such as DCS [ 22 ] proving only suitable for the detection of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the CogEvo tool, which focuses on orientation games and attentional processes, is useful for assessing the early stages of cognitive impairment [ 21 ]. On the other hand, the DCS tool correctly discriminates patients with dementia but its ability to differentiate those with MCI from cognitively healthy older adults is not as good [ 22 ]. In terms of cognitive areas that are assessed as digital cognitive biomarkers, tests that analyze memory and executive functions are the most sensitive and promising for the detection of MCI and dementia [ 23 ].…”
Section: Introductionmentioning
confidence: 99%